Workshop on Planning of Environmentally Friendly Layouts, 9 -11 June 1993, Intan, Kuala Lumpur : [proceedings] - Workshop on Planning of Environmentally Friendly Layouts (1993 : Intan, Kuala Lumpur); Institut Tadbiran Awam Negara; Malaysian Institute of Planners (Kuala Lumpur : INTAN, 1993)
03